2016
DOI: 10.5851/kosfa.2016.36.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Physico-chemical and Microbial Quality during the Production of Pastırma Cured with Different Levels of Sodium Nitrite

Abstract: Pastırma, a dry-cured meat product, is produced from the whole muscle and/or muscles obtained from certain parts of beef and water buffalo carcasses. The purpose of this study was to determine the effects of different levels of sodium nitrite on changes in the physicochemical and microbial quality during the production of pastırma. The changes in residual nitrite, salt, pH, moisture, thiobarbutiric acid reactive substances (TBARS), colour (L*, a*, b*), total aerobic mesophilic bacteria (TAMB), lactic acid bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
6
12
0
Order By: Relevance
“…The mean value determined in the final product pastırma was below the upper limit of 6.0 determined by Turkish Food Codex Meat and Meat Products Notification ( Anonymous, 2012 ). In various studies, changes in the pH values are in parallel with our findings and they all increase during production process ( Aksu and Kaya, 2001a ; Aksu and Kaya, 2002a ; Aksu and Kaya, 2002c ; Aksu et al , 2016 ).…”
Section: Resultssupporting
confidence: 87%
“…The mean value determined in the final product pastırma was below the upper limit of 6.0 determined by Turkish Food Codex Meat and Meat Products Notification ( Anonymous, 2012 ). In various studies, changes in the pH values are in parallel with our findings and they all increase during production process ( Aksu and Kaya, 2001a ; Aksu and Kaya, 2002a ; Aksu and Kaya, 2002c ; Aksu et al , 2016 ).…”
Section: Resultssupporting
confidence: 87%
“…The pH value of the pastırma should be above 5.5 in terms of sensory characteristics (Kaban, ; Leistner, ). As in the present study, the pH value of the pastırma was reported to be above 5.5 in other studies (Aksu, Erdemir, & Çakıcı, ; Akköse, Ünal, Yalınkılıç, Kaban, & Kaya, ).…”
Section: Resultssupporting
confidence: 80%
“…The results clearly showed that LRCWE‐added cemen pastes had no significant effect ( p > .05) on microbiological counts of pastırma. M/S counts were consistent with studies reporting that the dominant flora in dry‐cured meat and pastırma were these microorganisms (Aksu et al, 2016a), and it was also determined that the addition of the extract had no effect on this bacterial group (Table 3). Our data for microbiological counts of pastırma was supported by Cakici et al.…”
Section: Resultssupporting
confidence: 88%
“…The effects of treatment and the production stages and storage time on the TBARS values of sliced meat and pastırma (AC, after adding cemen; BC, before adding cemen; RM, raw material) on microbiological counts of pastırma. M/S counts were consistent with studies reporting that the dominant flora in dry-cured meat and pastırma were these microorganisms (Aksu et al, 2016a), and it was also determined that the addition of the extract had no effect on this bacterial group (Table 3). Our data for microbiological counts of pastırma was supported by Cakici et al (2015) and Aksu andKaya (2001, 2005)'s previous observations.…”
Section: Changes In Microbiological Counts Of Pastırma With Lrcwesupporting
confidence: 87%
See 1 more Smart Citation